0.5
36/√3
b*ab = ab2 Suppose b*ab = ab + b2. Assume a and b are non-zero integers. Then ab2 = ab + b2 b = 1 + b/a would have to be true for all b. Counter-example: b = 2; a = 3 b(ab) = 2(3)(2) = 12 = ab2 = (4)(3) ab + b2 = (2)(3) + (2) = 10 but 10 does not = 12. Contradiction. So it cannot be the case that b = 1 + b/a is true for all b and, therefore, b*ab does not = ab + b2
negative 1/2
If you mean end point A is (3, 5) and midpoint of line AB is (-2, 8) then end point B is (-7, 11)
Using the distance formula the length of ab is 5 units
Using the distance formula the length of ab is 5 units
3
-2
We suspect that 'A' is not equal to 7 9, but that (7, 9) arethe coordinates of 'A'. Same for 'B'.If that's true, then the two points are 5 units apart.
-1/2 or -0.50
The length is 3*sqrt(5) = 6.7082, approx.
h
0.5
36/√3
If you mean endpoints of (-1, -3) and (11, -8) then the length works out as 13
b*ab = ab2 Suppose b*ab = ab + b2. Assume a and b are non-zero integers. Then ab2 = ab + b2 b = 1 + b/a would have to be true for all b. Counter-example: b = 2; a = 3 b(ab) = 2(3)(2) = 12 = ab2 = (4)(3) ab + b2 = (2)(3) + (2) = 10 but 10 does not = 12. Contradiction. So it cannot be the case that b = 1 + b/a is true for all b and, therefore, b*ab does not = ab + b2